Time's eye - Clarke, Arthur C. (Arthur Charles), 1917-2008 (Clarke, Arthur C. (Arthur Charles), 1917-2008. Time odyssey, 2005)
A mysterious glowing orb appears over Central Asia, ripping the Earth into conflicting eras of the past, present, and future, mingling UN peacekeepers from the year 2037 with military forces from past eras.